2018
DOI: 10.1111/jphs.12229
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Patients’ Views on Services Provided by Community Pharmacies

Abstract: Objectives The purpose of this study is to evaluate the attitude of the patients with diabetes towards and satisfaction with services provided by the community pharmacists in Tehran. Although there is no national guideline for diabetic disease management in Iran, pharmacists, as accessible and trained healthcare professionals, provide patients with consultation regarding medications, diet and physical activity. With the increasing number of patients with diabetes in Iran, it is needed to evaluate the patients’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 32 publications
(61 reference statements)
0
6
0
Order By: Relevance
“…Based on our previous systematic review [ 21 ] various pharmaceutical care approaches seem successful and effective in increasing patient adherence, controlling glucose levels, and improving diabetes understanding. Furthermore, numerous studies have demonstrated that the community pharmacist, as a health promoter, can play a critical role in diabetes prevention [ 34 , 36 , 37 , 38 , 41 , 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on our previous systematic review [ 21 ] various pharmaceutical care approaches seem successful and effective in increasing patient adherence, controlling glucose levels, and improving diabetes understanding. Furthermore, numerous studies have demonstrated that the community pharmacist, as a health promoter, can play a critical role in diabetes prevention [ 34 , 36 , 37 , 38 , 41 , 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several similar studies have assessed the diabetic satisfaction and expectations towards community-pharmacy services world-wide [ 14 , 15 , 22 , 23 , 24 , 28 , 29 , 35 , 38 , 40 , 45 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of community pharmacies in Iran as a developing country might be different than other developed countries, such as North American or West European countries. For instance, over 85 per cent of community pharmacies in Iran are privately owned by individual pharmacists (Mehralian et al , 2018), whereas in the USA, over 80 per cent of pharmacies are owned by mega size corporations, such as CVS, Walgreens, Rite Aie and Walmart (S.K and A, 2017). This means that majority of pharmacies in the USA are not falling under the definition of small businesses.…”
Section: Limitations and Further Researchmentioning
confidence: 99%
“…Diabetes mellitus (DM) is one of the most prevalent chronic conditions and is associated with signi cant disability, morbidity, and mortality (1) worldwide; similar to Saudi Arabia's condition with 23.7% estimated prevalence among the adult population which is one of the highest percentages across the world (2). This metabolic disorder (DM) manifests in two main forms: type 1 and type 2 diabetes (3). It has a rapidly rising prevalence in both developed and developing countries with more than 422 million people thought to be suffering from the disease globally in 2014 (4).…”
Section: Introductionmentioning
confidence: 99%